Fenofibrate differentially regulates PAI-1 gene expression via AMPK-dependent induction of orphan nuclear receptor SHP - Chanda, Dipanjan (2009)
Plasminogen activator inhibitor type I (PAI-1) is a marker of the fibrinolytic system, and serves as a possible predictor for hepatic metabolic syndromes. Fenofibrate, a peroxisome proliferator-activated receptor α (PPARα) agonist, is a drug used for treatments of hyperlipidemia. Orphan nuclear receptor small heterodimer partner (SHP) plays a key role in transcriptional repression of crucial genes involved in various metabolic pathways. In this study, we show that fenofibrate increased SHP gene expression in cultured liver cells and in the normal and diabetic mouse liver by activating the AMP-activated protein kinase (AMPK) signaling pathway in a peroxisome proliferator-activated receptor α (PPARα)-independent manner. Administration of transforming growth factor β (TGFβ) or a methionine and choline deficient (MCD) diet to induce the progressive fibrosing steatohepatitis model in C57BL/6 mice was significantly reversed by fenofibrate via AMPK-mediated induction of SHP gene expression with a dramatic decrease in PAI-1 mRNA and protein expression along with other fibrotic marker genes. No reversal was observed in SHP null mice treated with fenofibrate. Treatment with another PPARα agonist, WY14643, showed contrasting effects on these marker genes expressions in wild type and SHP null mice, demonstrating the specificity of fenofibrate in activating AMPK signaling. Fenofibrate exhibited a differential inhibitory pattern on PAI-1 gene expression depending on the transcription factors inhibited by SHP. CONCLUSION: By demonstrating that a PPARα-independent fenofibrate-AMPK-SHP regulatory cascade can play a key role in PAI-1 gene down-regulation and reversal of fibrosis, our study suggests that various AMPK activators regulating SHP might provide a novel pharmacologic option in ameliorating hepatic metabolic syndromes.